Pergeseran Makna Sumpah dalam Bahasa Indonesia - Anisa Wakidah; Dian Puspitasari; Mutiara Nur Shafira Aryandhini; Kristina Wulandari (TRANSFORMATIKA, 2019)
Oath is an official statement or a word used to prove the truth, and someone who takes an oath can make a curse for himself if it violates the pledge. But, in its use in the present era, the word oath no longer shows its sacredness but also indicates its use as slang in affirming something among young people. This research is focused on shifting the meaning of the word oath. This research is qualitative—research data in the form of sentences that contain the word oath. The data was obtained from social media, Twitter, and Facebook. Data collection methods used in the form of refer to the method of note-taking. Data analysis methods used in the form of a method of distribution with substitution techniques or dressing techniques. From this research, the result is that the word oath has a shift in meaning, expanding, or generalizing. The word oath, which was originally used as a sacred word, in the millennial era, is used as a word to convince others and express feelings.